Development of the College of Science digital scholarship commons with an integrated scholar profile - Emano, Judy Ann M.
The delicate and sensitive nature of science information is crucial, its organization and management is paramount; therefore, a good research data management (RDM) service necessary. RDM service helps researchers and faculty members save time, increase citations enhance reproducibility, preserve data, increase visibility to founding agencies, and networking (Miller, Miller & Phillips,2018). While RDM is becoming relevant and gaining a huge recognition within the scholarly community, understanding the research activities of the CS faculty and researchers were greatly help in the governance of the large amounts of research data produced by the college. The essential role of academic libraries involves its expertise in handling and managing data, because libraries are now actively involved in research data services that address the entire research data lifecycle (Frederick, 2019). Therefore, this project aims to develop an in-house institutional repository (IR) service for the University of the Philippines Diliman College of Science. This is an RDM service that offer the College of Science (CS) faculty and researches a platform to store, manage and share their scholarly works. Additionally, this IR is also for archiving, reusing and repurposing. To maintain the relevance and sustainability of the IR, managing and preserving digital data and making sure that data is stored efficiently and discoverable by our identified stakeholders and most specially utilized with confidence through authenticity and integrity (Miller et al., 2018).